Rise of wolf 8 : witnessing the triumph of Yellowstone's underdog - McIntyre, Rick (Greystone Books, 2019)
Yellowstone National Park was once home to an abundance of wild wolves--but park rangers killed the last of their kind in the 1920s. Decades later, the rangers brought them back, with the first wolves arriving from Canada in 1995. This is the incredible true story of one of those wolves. Wolf 8 struggles at first--he is smaller than the other pups, and often bullied--but soon he bonds with an alpha female whose mate was shot. An unusually young alpha male, barely a teenager in human years, Wolf 8 rises to the occasion, hunting skillfully, and even defending his family from the wolf who killed his father. But soon he faces a new opponent: his adopted son, who mates with a violent alpha female. Can Wolf 8 protect his valley without harming his protégé? Authored by a renowned wolf researcher and gifted storyteller, The Rise of Wolf 8 marks the beginning of an original and bold new trilogy, which will transform our view of wolves forever.